A educação musical: o saber corporal aprendido por meio da educação/técnica vocal para bailarinos contemporâneos - Pereira, Daiana Felix (Universidade do Vale do Rio dos Sinos, 2012)
This work investigates the process of educating the voice of contemporary dancers through vocal and body movement education. It seeks to understand how teaching dance and music historically disassociate itself from the body of the learner. Related to this question of contemporary dance training methods is also the question of gender roles and in particular that of male dominance. This thesis examines the historical trajectory of dance, weaving in issues of gender in relation to concepts such as education of the body, and the process of movement, as well as the topic of sexuality and how dance is often interpreted in terns of erotic feelings. This theoretical study looks at two essays in depth: the first is an analysis of Rousseau’s Chapter V (1712 - 1778), "From Emile, or Education, proposing a possible dance between Emilio and Sofia. The second essay is concerned with recording dancers and singers who train to use their body and voice simultaneously and aim to understand the processes involved that connect these two forms. This paper points to a new language and pedagogy that highlights the relationship and union between dance and voice, and the body as an art.
Keywords: Dança contemporânea; Educação vocal; Corpo; Processos; Contemporary dance; Vocal education; Body processes; ACCNPQ::Ciências Humanas::Educação